Urea and Tannin in multiple supplements: Ingestive behavior of grazing beef cattle - Araújo, Hellen Patricia De Oliveira; Paula, Nelcino Francisco De; Martello, Hariany Ferreira; Teobaldo, Ronyatta Weich [UNESP]; Pereira, Luana Barros; Mora, Lays Martins; Valentim, Jean Kaique; Antunes, Hellen Cristina Ferreira (Editora da Universidade Estadual de Maringá - EDUEM, 2020)
This work was carried out to evaluate the inclusion of urea and tannin in multiple supplements on ingestive behavior of cattle in pasture. The experiment was taken in the Cattle Nutrition pasture of the Experimental Farm of the Federal University of Mato Grosso, in 4 x 4 Latin square design with a factorial arrangement 2 x 2 (with and without urea and with and without tannin). Four Nellore bulls were used, with average weight of 470 kg and an average age of 20 months, randomly divided in: Supplement without urea and without tannin, Supplement without urea and with tannin, supplement with urea and without tannin, and supplement with urea and with tannin. The level of supplementation used was 1% of body weight during the dry period of the year. The experiment lasted 80 days in total, divided into four periods of 20 days each and every where, the 14 first days were intended for the adaptation of animals to the add-in and the 6 days left to collect samples. Bulls were visually observed for two days during 12 consecutive hours, morning and evening shifts recital. The variables studied were: grazing time, idle time, time of rumination, length of stay in the trough and length of stay at a watering hole.The inclusion of urea to cattle supplement in grazing reduced the grazing time and increased time spent in the trough. The addition of tannin did not influence ingestive behavior.
Keywords: natural additives; forage; supplementation; urea; tannins